1987
DOI: 10.4049/jimmunol.138.4.1051
|View full text |Cite
|
Sign up to set email alerts
|

The B cell is the initiating antigen-presenting cell in peripheral lymph nodes.

Abstract: We have examined the role of B cells in antigen presentation in lymph nodes in several ways. We found that mice depleted of B lymphocytes via chronic injection of anti-mu-chain antibody do not mount peripheral lymph node T cell proliferative responses to normally immunogenic doses of antigen. Depletion of B cells by passage of immune lymph node cells over anti-immunoglobulin columns early after immunization depletes antigen-presenting function from draining lymph nodes, and this function can be restored by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The B-cell subsets, once mature and terminally differentiated into plasma and effector cells, are mainly involved in circulating antibodies secretion, thymic-independent IgM antibody responses and antigen presentation [ 40 , 41 ]. B lymphocytes are required for the initiation of T-cell immune responses, and recent studies have demonstrated that their absence impairs CD4+ T-cell priming [ 42 ]. The differential activation and expansion of CD4+ T cells by B lymphocytes could be associated with immune responses, making this a critical area for future studies of host defense and autoimmunity.…”
Section: Background Of B Lymphocytesmentioning
confidence: 99%
“…The B-cell subsets, once mature and terminally differentiated into plasma and effector cells, are mainly involved in circulating antibodies secretion, thymic-independent IgM antibody responses and antigen presentation [ 40 , 41 ]. B lymphocytes are required for the initiation of T-cell immune responses, and recent studies have demonstrated that their absence impairs CD4+ T-cell priming [ 42 ]. The differential activation and expansion of CD4+ T cells by B lymphocytes could be associated with immune responses, making this a critical area for future studies of host defense and autoimmunity.…”
Section: Background Of B Lymphocytesmentioning
confidence: 99%
“…Priming and clonal expansion of naïve CD4 + T cells. Although naïve T-cell responses are normally primed by dendritic cells, B cells are also very efficient antigenpresenting cells (APC) and have been postulated to play important roles in the initial T cell priming (45)(46)(47)(48)(49)(50). While not fully understood, B cells are also likely to play important roles in the reactivation of memory responses, and the continued stimulation and expansion of primary responses may be assisted by activated B cells (50)(51)(52)(53)(54).…”
Section: The Following Effects Of B Cells On T Cells Have Been Describedmentioning
confidence: 99%